Fostering Entrepreneurship Education within South African Higher Education - Mmakola, Sharon Dipolelo; Maphalala, Mncedisi Christian (Journal of Economics Education and Entrepreneurship, 2025)
The paper explores the imperative of fostering entrepreneurship education within the context of South African higher education. The escalating unemployment rate in South Africa caused by economic challenges necessitates sustainable pathways to alleviate unemployment. Higher education institutions are called upon to play a pivotal role in cultivating entrepreneurial competencies among students. There is urgency of aligning educational practices with the economic demands of the country, emphasising entrepreneurship education as a strategic catalyst for fostering self-reliance and job creation; considering the country's socio-economic landscape, historical context, and the imperative for inclusive economic participation. The findings reveal that the key components of effective entrepreneurship education, encompasses curriculum design, pedagogical approaches, experiential learning, and collaboration with industry and communities. It is also important to stress the role of technology and digital literacy in shaping entrepreneurial competencies, considering the rapid technological advancements that influence the contemporary entrepreneurial landscape.